ADIPOCYTOKINES AND OBESITY-LINKED DISORDERS - OUCHI, NORIYUKI (Nagoya J Med Sci, 2012)
Obesity is closely associated with an increased risk for metabolic and cardiovascular diseases. Adipose tissue produces a number of secretory bioactive substances, also known as adipocytokines or adipokines, which directly affect adjacent or distant organs. Most adipocytokines are pro-inflammatory, thereby promoting the obesity-linked disorders. In contrast, there are a small number of adipocytokines that exhibit anti-inflammatory properties. It is now recognized that dysregulated production or secretion of adipocytokines caused by adipocyte dysfunction leads to the development of obesity-linked complications. In this review, we focus on the functional role of several adipocytokines in metabolic and cardiovascular diseases.